Policy on Irregular Migrants in Malaysia: An Analysis of its Implementation and Effectiveness - Azizah Kassim; Ragayah Haji Mat Zin (Philippine Institute for Development Studies (PIDS), 2011)
In the early 1970s, Malaysia began to be inundated by foreign workers, all of whom were irregular migrants. A decade later their uncontrolled entry left several negative consequences especially to the internal and border security of the country. To overcome the problems, Malaysia introduced the foreign worker policy which became fully implemented in 1992. The policy has two objectives, firstly to regulate the inflow of foreign workers; and secondly, to stem the inflow of irregular migrant workers into the country. The implementation of the policy has led to a spectacular increase in the number of legally recruited migrant workers. However, it has not been able to curb the expansion of irregular migrants; instead their number has risen in parallel with that of legally recruited ones. This report is an attempt to examine why this is so. It is based on a research carried out in 2011 among 404 irregular migrants as respondents, comprising 340 who were apprehended and housed at seven of the 17 holding depots run by the government and 64 others who are still at large.
Keywords: 330; migrant workers; immigration; emigration; foreign workers; irregular migrants; illegal immigrants; legalization; amnesty; deportation; asylum seekers; refugees; Arbeitsmigranten; Illegale Migration; Asylrecht; Migrationspolitik; Malaysia